Sickle cell hepatopathy - Bandyopadhyay Ranjana; Bandyopadhyay Sanjay; Dutta Anita (Wolters Kluwer Medknow Publications, 2008)
Sickle cell hepatopathy is a well-documented entity that ranges from the self-limiting hepatic right upper quadrant syndrome to the potentially lethal intrahepatic cholestasis and acute hepatic sequestration syndromes. We describe a 26-year-male with homozygous sickle cell disease who had this unique hepatic presentation and was documented to have characteristic findings of cholestasis, portal inflammation and sinusoidal dilatation on histopathology.